2019
DOI: 10.2135/tppj2018.12.0010
|View full text |Cite
|
Sign up to set email alerts
|

Using R‐Based Image Analysis to Quantify Rusts on Perennial Ryegrass

Abstract: Core Ideas An automated open‐source analysis system was developed to rate crown and stem rust. The system was validated against manual measurements and visual rater ability. Consistency in rater (n = 9) ability was excellent for crown rust and fair to good for stem rust. Agreement in rater scores for individual images was low and showed high levels of variation. The automated system can replace visual rating of crown rust in the field but not stem rust. Crown and stem rust are major diseases of perennial rye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…The results for crown rust showed that computer‐estimated severity was much lower than visual severity, which corresponds to the findings of Heineck et al. (2019). Image analysis has several benefits over visual estimates, including lower employee skill level requirements and the permanent recording of digital phenotypes that can be analyzed at any time throughout the year (Bade & Carmona, 2011; Sherwood, Berg, Hoover, & Zeiders, 1983) with repeatable R scripts and training data that can be shared within and among research groups.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The results for crown rust showed that computer‐estimated severity was much lower than visual severity, which corresponds to the findings of Heineck et al. (2019). Image analysis has several benefits over visual estimates, including lower employee skill level requirements and the permanent recording of digital phenotypes that can be analyzed at any time throughout the year (Bade & Carmona, 2011; Sherwood, Berg, Hoover, & Zeiders, 1983) with repeatable R scripts and training data that can be shared within and among research groups.…”
Section: Resultssupporting
confidence: 89%
“…For instance, as plant density increased from three plants m −2 (SPN) to 5,000 plants m −2 (TGS), mean severity increased by more than 100‐fold from 0.01 to 1.6% rust pustule coverage of healthy tissue. These more conservative severity estimates in general may seem very small; however, the computer was trained to detect crown rust pustules, which excludes the necrotic or chlorotic leaf tissue that often inflate visual estimates (Heineck et al., 2019; Sherwood et al., 1983). Proliferation of disease severity such as crown rust as a result of plant density are axiomatic in epidemiology and are caused by increased inoculum load and moisture within the plant canopy (Burdon & Chilvers, 1982).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual ratings have long proven effective; however, data taken by several raters on the same experimental unit over time have been shown to be imprecise for several foliar pathogens including Puccinia spp. (Heineck, McNish, Jungers, Gilbert, & Watkins, 2019;Sherwood, Berg, Hoover, & Zeiders, 1983). Therefore, quantitative ratings using image analysis can be used to reinforce visual ratings in the field to provide more accurate insight into endophyte effects.…”
Section: Crop Sciencementioning
confidence: 99%
“…Quantification of rust severity was conducted using an automated system described by Heineck et al (2019) for both five-leaf samples and whole plants. Image analysis was done using ImageJ and R (Schneider, Rasband, & Eliceiri, 2012; Version 3.5.0; R Core Team, 2018).…”
Section: Image Analysis For Crown Rustmentioning
confidence: 99%